The assessment of the tear film lipid layer in different types of dry eye syndrome - T.N. Safonova; V.V. Averich; E.S. Medvedeva (РМЖ "Клиническая офтальмология")
T.N. Safonova, V.V. Averich, E.S. Medvedeva M.M. Krasnov Research Institute of Eye Diseases, Moscow, Russian Federation Aim: to assess the tear film (TF) lipid layer in different types of dry eye syndrome. Patients and Methods: this study included 60 patients (120 eyes), 20–35 years old: group 1 consisted of 20 patients (40 eyes) with a verified diagnosis of burning eye syndrome (BES) and group 2 consisted of 20 patients (40 eyes) with an established diagnosis of dry eye syndrome (DES). Group 3 (control) comprised 20 individuals (40 eyes) of the same age range, who did not have any somatic or eye diseases. The results of thiascopy in the control group individuals were considered conditionally normal findings. The exclusion criterion used in the study was the presence of clinical signs of blepharitis and meibomian gland dysfunction (MGD) in patients and individuals of the control group. The evaluation of all patients included determining the number of blinking movements and the completeness of eyelid closure, conducting the Norn's test, and using an improved thiascopy method. The computed analysis of the obtained digital images was performed with "Lacrima" software. Results: in 70% of cases, an incomplete eyelid closure was detected in the group of patients with BES, while the multiplicity of blinking movements was within the normal range. The Norn's test measurements in the group of patients with BES were 12 seconds, in the group of patients with DES — 7 seconds, and in the control group — 15 seconds. The absence of TF sections with a lipid layer exceeding 0.5 microns (p<0.05); a 2.5-fold decrease in the zone with a lipid layer thickness of 0.13 — 0.27 µm a 3-fold decrease in the zone with a lipid layer thickness of 0.27 — 0.5 µm; and a 12% increase in the uncertainty zone were reported in the group of patients with BES compared to those in the group of patients with DES. Conclusion: changes in the tear film lipid layer were more pronounced in patients with BES. Keywords: dry eye syndrome, burning eye syndrome, tear film, Lacrima, thiascopy, cationic emulsion, lipid-containing agents. For citation: Safonova T.N., Averich V.V., Medvedeva E.S. The assessment of the tear film lipid layer in different types of dry eye syndrome. Russian Journal of Clinical Ophthalmology. 2023;23(1):9–13 (in Russ.). DOI: 10.32364/2311-7729-2023-23-1-9-13.